The Effects of Service Quality Dimensions on Customer Loyalty - Lee, Zhao Li (2010)
Nowadays, advances in technology coupled with increasing labour costs have eventually caused service firms to explore self-service delivery options. In line with this, the financial industry is of no exception being influenced as well. Apparently, the Internet seems to be the ideal medium for carrying banking activities due to its high speed of information transmission and cost savings potential. Therefore, from a technological and cost-driven standpoint it may seem quite rational for banks to shift as many banking activities online as possible. Furthermore, Internet banking is also regarded as one of the most popular services utilised by the Malaysian retail banking customers in recent years. Despite its attractiveness, the question of how to foster customer loyalty arises when the relationship between the bank and the customer becomes a virtual one. Most importantly, the challenge faced by banks these days in using the Internet as one of its distribution channel is how to effectively manage service quality. Accordingly, many past studies have shown that the quality of online service is the core issue that influences customers' loyalty towards the Internet banking services worldwide. Therefore, the aim of this thesis is to find out the various service quality dimensions that affect customer loyalty in the Internet banking context of Malaysia. With the assistance of a structured questionnaire, primary data was collected from Internet banking users of both private and public banks. A total sample of 200 respondents who actually used Internet banking was selected by following non-probabilistic convenience sampling technique as it is approriate for descriptive studies. Data presentation and analysis were done with the help of various statistical tools, such as descriptive analyses, explanatory factor analysis, reliability analysis, and multiple regresion analysis using SPSS. Several hypotheses were tested concerning the relationships between service quality dimensions and customer loyalty. Findings revealed that reliability, security, customisation, and design of the user interface were essential in keeping customers loyal, with security having the most significant impact. Alternatively, responsiveness was found to be insignificant in affecting customer loyalty. Accordingly the results of the analysis and the implications are discussed. Lastly, recommendations are made in order to improve Internet banking service quality in Malaysia.